Pubescenes, jatrophane diterpenes, from Euphorbia pubescens, with multidrug resistance reversing activity on mouse lymphoma cells - Valente, C (2015)
The macrocyclic jatrophane diterpene polyesters, pubescenes A-D (1-4) were isolated from the whole dried plant of Euphorbia pubescens, and evaluated for multidrug resistance (MDR) reversing activity on mouse lymphoma cells. All the compounds displayed very strong activity compared with the positive control verapamil. Pubescene D (4) is a new compound, whose structure was established as 3beta9alpha,-diacetoxy-7beta-benzoyloxy-15beta-hydroxy-14-oxo-2betaH-jatropha-5E,12E-diene by spectroscopic methods, including H-1-H-1 COSY, HMQC, HMBC and NOESY.